МОДЕЛЮВАННЯ ВИХРОВОГО ДОПАЛЮВАННЯ ПРОДУКТІВ ГАЗИФІКАЦІЇ БІОМАСИ В ТОПЦІ З КИПЛЯЧИМ ШАРОМ - Kobzar, S; Borisov, I; Khalatov, A.; Teplitski, A.; Pitsukha, Y. (Institute of Engineering Thermophysics of NAS of Ukraine, 2021)
CFD modeling of the afterburning of biomass gasification products in a fluidized bed furnace with a vortex supply of secondary air has been carried out. The effect of secondary air heating on the ecological characteristics of flue gases has been determined. Modeling has shown that gasification products swirl in the primary chamber with the formation of a central vortex, which obeys the law of solid-body rotation. An increase in the temperature of the secondary air leads to an increase in its tangential velocity and, as a consequence, to an increase in centrifugal mass forces. Calculations have shown that with an increase in the secondary air temperature, the maximum of the kinetic energy of turbulence shifts to the periphery and increases in absolute value. This results in more efficient mixing of the central (producer gas) and peripheral (secondary air) streams. As a result, this leads to a more complete combustion. The influence of secondary air heating on the ecological characteristics of the furnace has been determined. As a result of air heating from 30° C to 300° C, the concentration of carbon monoxide decreases by more than 1.5 times. The concentration of nitrogen oxides practically does not change and amounts to 3.5 mg /nm3.